Effects of Self-Enhancement on Eye Movements During Reading - Lou, Ya; Cai, Huajian; Liu, Xuewei; Li, Xingshan (Frontiers in Psychology, 2019)
Previous studies show that readers’ eye movements are influenced by text properties and readers’ personal cognitive characteristics. In the current study, we further show that readers’ eye movements are influenced by a social motivation of self-enhancement. We asked participants to silently read sentences that describe self or others with positive or negative traits while their eyes were monitored. First-fixation duration and gaze duration were longer when positive words were used to describe self than to describe others, but with no corresponding effect for negative words. These results therefore suggest that eye movements can be influenced by the motivation of self-enhancement in addition to various stimuli features and cognitive factors. This finding indicates that eye movements are sensitive to high level cognitive processes such as self enhancement, and therefore the eye movement methodology can potentially be used to study implicit social cognition.